Implementasi Simulasi 3D Menggunakan Virtual Reality Berbasis Android Untuk Tour Universitas Pamulang - Ade Yuliova Balok; Niki Ratama (CV. Multi Kreasi Media, 2023)
A virtual tour is a variety of 360-degree simulations that consist of multiple shapes of 3D models of buildings and objects shaped to look realistic. The presentation of the 3D model involves creating a 3D model of the object required in this case. Guilde Tour allows users to access information without having to be physically present. In addition, VR media allows you to introduce the Pamulang University building. 3D media must also be supported with appropriate details for projecting because this media is the main purpose of intermediaries in the digital information transmission process. Application testing is carried out using usability testing with respondents taken based on purposive side-by-side techniques and using a questionnaire. The results obtained based on usability testing can be concluded that the application is easy to use.